Long-term cost–effectiveness of Oncotype DX® versus current clinical practice from a Dutch cost perspective. (September 2015) - Kip, Michelle; Monteban, Helma; Steuten, Lotte
Introduction: This study analyzes the incremental cost–effectiveness of Oncotype DX ® testing to support adjuvant chemotherapy recommendations, versus current clinical practice, for patients with estrogen receptor-positive (ER + ), node-negative or micrometastatic (pN1mic) early-stage breast cancer in The Netherlands.Methods: Markov model projecting distant recurrence, survival, quality-adjusted life years (QALYs) and healthcare costs over a 30-year time horizon.Results: Oncotype DX was projected to increase QALYs by 0.11 (0.07–0.58) and costs with €1236 (range: -€142–€1236) resulting in an incremental cost–effectiveness ratio of €11, 236/QALY under the most conservative scenario.Conclusion: Reallocation of adjuvant chemotherapy based on Oncotype DX testing is most likely a cost-effective use of scarce resources, improving long-term survival and QALYs at marginal or lower costs.